STRATEGI GURU PENDIDIKAN AGAMA KRISTEN DALAM MENANAMKAN KARAKTER PEDULI PADA PESERTA DIDIK DI SD NEGERI SAYANGAN SURAKARTA - Damai Indah Chrisgita Cahyani; Dian Paula April Juwan (STKIP Subang, 2026)
This study aims to describe the strategies implemented by Christian Religious Education teachers in instilling caring character among students at SD Negeri Sayangan Surakarta. This research employed a qualitative descriptive approach with a case study design. The research participants consisted of one Christian Religious Education teacher, one principal, one third-grade homeroom teacher, and ten third-grade students selected through purposive sampling. Data were collected through interviews, observations, and documentation. The data were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings revealed that the strategies used by Christian Religious Education teachers to instill caring character included integrating Christian values into classroom learning, providing exemplary behavior, implementing habituation activities, encouraging cooperation among students, and offering guidance and motivation. These strategies were supported by the school's culture, which promotes respect, empathy, responsibility, and mutual care among students. The study concludes that the consistent implementation of these strategies contributes positively to the development of students' caring character in their daily lives.